1996
DOI: 10.1128/mcb.16.10.5616
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila P-Element KP Repressor Protein Dimerizes and Interacts with Multiple Sites on P-Element DNA

Abstract: Drosophila P elements are mobile DNA elements that encode an 87-kDa transposase enzyme and transpositional repressor proteins. One of these repressor proteins is the 207-amino-acid KP protein which is encoded by a naturally occurring P element with an internal deletion. To study the molecular mechanisms by which KP represses transposition, the protein was expressed, purified, and characterized. We show that the KP protein binds to multiple sites on the ends of P-element DNA, unlike the full-length transposase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 37 publications
5
106
0
Order By: Relevance
“…This polypeptide would therefore be shorter than the KP polypeptide, which has 207 amino acids and contains the first 199 amino acids of the transposase. In vitro studies have shown that the KP polypeptide represses transposase activity in a concentration-dependent manner by binding competitively to specific sequences in a target P element (Lee et al 1996(Lee et al , 1998. A DNA-binding domain near the amino terminus of the polypeptide is essential for this repression, and two dimerization domains located between amino acids 101 and 207 facilitate it.…”
Section: Discussionmentioning
confidence: 99%
“…This polypeptide would therefore be shorter than the KP polypeptide, which has 207 amino acids and contains the first 199 amino acids of the transposase. In vitro studies have shown that the KP polypeptide represses transposase activity in a concentration-dependent manner by binding competitively to specific sequences in a target P element (Lee et al 1996(Lee et al , 1998. A DNA-binding domain near the amino terminus of the polypeptide is essential for this repression, and two dimerization domains located between amino acids 101 and 207 facilitate it.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, M 0 strains vary from extremely high to moderately low P susceptibility (AnxolabĂ©hĂšre et al, 1985) and possess from a few to 50 copies per genome (AnxolabĂ©hĂšre et al, 1984;Black et al, 1987), most of which, if not all, are defective sequences (Bingham et al, 1982;Black et al, 1987). Among them, the most frequently deleted derivative is KP, a type II element (deleted at positions 808-2560) that encodes a 207 aa protein that has been considered as an important repressor of transposition (Lee et al, 1996;Simmons et al, 2002). D. melanogaster populations show different ratios of full-sized and defective P elements, and their frequencies and P-M phenotypes vary worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…To explain frequent local insertion (Zhang and Spradling 1993), proteins bound to P-element termini (Lee et al 1996;Beall and Rio 1998;Tang et al 2005) are thought to tether the excised element to the unexcised copy on the sister chromatid, giving rise to a local insertion event near the starting element. An alternative explanation is that local transposition may occur shortly after DNA replication, during which the two copies of the P elements are still in a close association.…”
Section: Resultsmentioning
confidence: 99%